ASEAN Economic Co-operation and Challenges - Low, Linda (Book collections on Project MUSE., 2004)
This book is written in an easily understood style. It explains the background of the orgin of ASEAN (Association of Southeast Asian Nations) of which there are 10 member-countries. The author looks at the progress made, as well as the problems that the association faces ...